Muscular Oxygen Uptake Kinetics in Aged Adults - Koschate, J.; Drescher, U.; Baum, K.; Eichberg, S.; Schiffer, T.; Latsch, J.; Brixius, K.; Hoffmann, U. (International Journal of Sports Medicine, 2016)
Pulmonary oxygen uptake (V˙O2) kinetics and heart rate kinetics are influenced by age and fitness. Muscular V˙O2 kinetics can be estimated from heart rate and pulmonary V˙O2. In this study the applicability of a test using pseudo-random binary sequences in combination with a model to estimate muscular V˙O2 kinetics was tested. Muscular V˙O2 kinetics were expected to be faster than pulmonary V˙O2 kinetics, slowed in aged subjects and correlated with maximum V˙O2 and heart rate kinetics. 27 elderly subjects (73±3 years; 81.1±8.2 kg; 175±4.7 cm) participated. Cardiorespiratory kinetics were assessed using the maximum of cross-correlation functions, higher maxima implying faster kinetics. Muscular V˙O2 kinetics were faster than pulmonary V˙O2 kinetics (0.31±0.1 vs. 0.29±0.1 s; p=0.004). Heart rate kinetics were not correlated with muscular or pulmonary V˙O2 kinetics or maximum V˙O2. Muscular V˙O2 kinetics correlated with maximum V˙O2 (r=0.35; p=0.033). This suggests, that muscular V˙O2 kinetics are faster than estimates from pulmonary V˙O2 and related to maximum V˙O2 in aged subjects. In the future this experimental approach may help to characterize alterations in muscular V˙O2 under various conditions independent of motivation and maximal effort.
Keywords: exercise capacity; pseudo-random binary sequences; cardiorespiratory kinetics